Peramalan Curah Hujan Menggunakan Metode High Order Fuzzy Time Series Multi Factors - Ahmada Bastomi Wijaya; Candra Dewi; Bayu Rahayudi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Malang Regency is one of the regencies in East Java which has a high level of agricultural production in almost every district has agricultural land. The problem is when high rainfall is not a few farmers who experienced crop failure. Rainfall is one of several factors that affect climate change so it is very important to determine the yields obtained. The problem of this harvest failure can be overcome by forecasting rainfall, with rainfall forecasting farmers can determine the time of the appropriate cropping patterns so as to anticipate the occurrence of crop failure. On the research of forecasting rainfall in dasarian based on several factors namely temperature, humidity, and wind speed. The methods used for forecasting rainfall dasarian is a High-Order Fuzzy Time Series Multi factors. In this method the formation of subinterval using fuzzy C-means. In calculating the error of forecasting result using Mean Square Error (MSE). Based on the results of tests conducted the smaller threshold and the greater data training as well order the value error is obtained increasingly low. The result of forecasting dasarian rainfall for forecasting one year ahead using this method get the best MSE result of 539,698.